«Таянч масала»лар ёрдамида талабалар фаоллигини ошириш методикаси - Ашурова, Д.Н. (SCIENCE and SOCIETY, 2020)
The article is devoted to the study of the consecutive approach and intergrated methods with "Basic tasks" that promote to improving students’ activeness at higher educational institutions.
Keywords: innovative program and didactic complex; methods of "Basic tasks"; principles of supporting tasks